A Case study of Mitigating Risk of Invoice Payment Failure At Electricity Provider Company using the House of Risk Method - Widyasari Retnaningtyas; Niniet Indah Arvitrida (Journal of Advances in Information and Industrial Technology, 2025)
Considering that a complicated or delayed invoice payment process can disrupt business operations, the company must establish mitigation measures to prevent such occurrences and minimize potential failures that may hinder future business processes. This context specifically involves collaboration with business partners or vendors providing services and materials. This research aims to map out the activities within the invoice payment business process, identify risk events and related risk agents, and formulate mitigation strategies to reduce their negative impact. The House of Risk (HOR) method is utilized to prioritize risks according to Aggregate Risk Potential (ARP) scores then the scores will be classified with a Pareto diagram. This study aims to offer actionable recommendations for risk mitigation, mostly in digitalization and automation of systems that can help lower the rate of document rejections and accelerate the overall payment cycle. Ultimately, these improvements will contribute to increased operational efficiency and reinforce vendor confidence, ensuring that high-value invoices are processed more reliably and promptly.